ASSESSMENT OF TIDAL ENERGY RESOURCES IN BALI STRAIT - Andi Muhammad Alfian Arafat; Yassir Arafat (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
The ocean possesses advantages as a sustainable and predictable source of energy, with tidal energy being one such marine-derived energy source. This study examines the analysis of ocean energy potential in the study location of the Bali Strait. The analysis of tidal energy potential follows the guidelines of the European Marine Energy Center (EMEC) and employs numerical modeling to identify current velocities using Delft3D. This study investigates the influence of water depth columns to determine the optimal depth for the placement of energy conversion technologies. It is found that the highest current velocities occur in the strait's narrowed section. Furthermore, from the analysis of tidal energy potential, it is determined that upper water depth columns (9 m, 19 m, and 26 m) can generate twice as much energy as the lower water depth columns (40 m and 45 m).